2020
DOI: 10.1002/adma.201905756
|View full text |Cite
|
Sign up to set email alerts
|

Cation–π Interactions in Graphene‐Containing Systems for Water Treatment and Beyond

Abstract: was also recognized. [2] In addition to these forces, one intriguing noncovalent interaction: cation-π interaction, has emerged as an intermolecular force of great significance in chemistry, biology, and materials science. [3] The cation-π interactions basically refers to the interplay between cations and the π electron cloud of an aromatic system. It plays a great role in biological systems for molecular recognition, protein-protein interactions, and the maintenance of macromolecular structures. It also occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 225 publications
(145 reference statements)
1
79
0
2
Order By: Relevance
“…The UV-vis absorption spectra (see Figure S2c) showed that the characteristic peaks at ≈230 nm were attributed to π-π* from the aromatic rings. The results are consistent with the previous reports [27,[36][37][38].…”
Section: Characterizations Of the Ah-rgosupporting
confidence: 94%
“…The UV-vis absorption spectra (see Figure S2c) showed that the characteristic peaks at ≈230 nm were attributed to π-π* from the aromatic rings. The results are consistent with the previous reports [27,[36][37][38].…”
Section: Characterizations Of the Ah-rgosupporting
confidence: 94%
“…When GO is reduced to rGO during the hydrothermal process, rGO tends to interact with adjacent rGOs through hydrophobic and π-π interactions which trigger the aggregation of the rGO sheets. [20] Interestingly, the polydopamine coating on the rGO sheets prevents such aggregation of the rGO sheets probably due to the various hydrophilic oxygen and nitrogen functional groups of polydopamine. Furthermore, energy-dispersive X-ray (EDX) mapping about carbon, oxygen, and nitrogen for TDPD confirmed a homogeneous coating of polydopamine on the GO sheets ( Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…10). When the roots of maize seedlings grown in soil are exposed to gaphene, the N and K contents of soil would be elevated because of the cation-π interactions in graphene, which lead to the accumulation of cations on the graphene surface [65]. Thus, the transporters in the root (such as Nitrate transporter, nrt2.2; potassium transporter 5, HAK20) may recognize the corresponding signals and trigger the expression increase of transporter genes, and the change of phytohormones, including auxin, cytokinin and gibberellin, and so on.…”
Section: Graphene-related Transcription Factor Genes Inz Maysmentioning
confidence: 99%